1987
DOI: 10.1128/jb.169.12.5887-5890.1987
|View full text |Cite
|
Sign up to set email alerts
|

Control of glycolysis by glyceraldehyde-3-phosphate dehydrogenase in Streptococcus cremoris and Streptococcus lactis

Abstract: The decreased response of the energy metabolism of lactose-starved Streptococcus cremoris upon readdition of lactose is caused by a decrease of the glycolytic activity (B. Poolman, E. J. Smid, and W. N. Konings, J. Bacteriol. 169:1460-1468. The decrease in glycolysis is accompanied by a decrease in the activities of glyceraldehyde-3-phosphate dehydrogenase and phosphoglycerate mutase. The steady-state levels of pathway intermediates upon refeeding with lactose after various periods of starvation indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 13 publications
6
54
2
Order By: Relevance
“…Although the loss of glycolytic activity could be correlated with specific loss of glyceraldehyde 3-phosphate dehydrogenase, phosphoglycerate mutase and pyruvate kinase activity, two-dimensional gel analyses indicated that overall protein degradation is non-specific during starvation. In a previous study (Poolman et al 1987b) it has been shown that during lactose starvation of L. lactis subsp, cremoris Wg2 glyceraldehyde 3-phosphate dehydrogenase is inactivated but not (specifically) degraded. A similar situation may hold for L. lactis The analysis of arginine/ornithine exchange activities in membrane vesicles isolated from growing and starving cells indicates that the transport system is not inactivated during starvation; rather a slight increase in exchange activity is observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the loss of glycolytic activity could be correlated with specific loss of glyceraldehyde 3-phosphate dehydrogenase, phosphoglycerate mutase and pyruvate kinase activity, two-dimensional gel analyses indicated that overall protein degradation is non-specific during starvation. In a previous study (Poolman et al 1987b) it has been shown that during lactose starvation of L. lactis subsp, cremoris Wg2 glyceraldehyde 3-phosphate dehydrogenase is inactivated but not (specifically) degraded. A similar situation may hold for L. lactis The analysis of arginine/ornithine exchange activities in membrane vesicles isolated from growing and starving cells indicates that the transport system is not inactivated during starvation; rather a slight increase in exchange activity is observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were broken by cycle sonication (8 x 15 s with 45-s intervals; amplitude intensity of 8 gm) under mtrogen at 4 ~ To remove the cell debris the extracts were centrifuged for 60 rain at 48000 • g at 4 ~ The enzymatic activities in the cell lysates were determined by standard procedures involving NAD(H)-or NADPcoupled assays (Bergmeier 1974), essentially as described by Poolman et al (1987b).…”
Section: Enlvmatic Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…therefore has a key role in glycolysis. This has been underscored by metabolic studies which showed that the decrease in glycolytic activity observed after starved L. lactis cells were provided with an energy source was primarily due to diminished glyceraldehyde-3-phosphate dehydrogenase activity (Poolman et a/., 1987). Since the publication of the amino acid sequence of lobster glyceraldehyde-3-phosphate dehydrogenase (Davidson e t al., 1967), the primary structures and predicted sequences of glyceraldehyde-3-phosphate dehydrogenases from many organisms have been reported, and all of the sequences share considerable similarity (Fothergill-Gilmore & Michels, 1993).…”
Section: Introductionmentioning
confidence: 97%